1951
DOI: 10.1063/1.1745921
|View full text |Cite
|
Sign up to set email alerts
|

A High Intensity Source for the Molecular Beam. Part I. Theoretical

Abstract: In a standard molecular beam source the maximum attainable intensity in the collimated beam is limited first by the effusion rate through the oven slit, which must be made sufficiently narrow to attain free molecule flow, and second by unfavorable geometrical factors encountered in selecting a collimated beam from random initial velocities. This paper will propose that the first slit be placed in the flow from a miniature high velocity nozzle coaxial with the final beam. The nozzle converts part (∼¾ for a Mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
5

Year Published

1966
1966
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(116 citation statements)
references
References 1 publication
1
109
0
5
Order By: Relevance
“…Here, instead of raising the pressure directly around the ion inlet of the mass spectrometer, the high pressure ion source was separated from the first pumping stage with an additional stage at near atmospheric pressure. The arrangement is like a nozzle-skimmer system [10], where the ions exit from the high pressure stage via a nozzle to an open space at~1 atm and re-enter to the vacuum through the ion sampling skimmer.…”
Section: Introductionmentioning
confidence: 99%
“…Here, instead of raising the pressure directly around the ion inlet of the mass spectrometer, the high pressure ion source was separated from the first pumping stage with an additional stage at near atmospheric pressure. The arrangement is like a nozzle-skimmer system [10], where the ions exit from the high pressure stage via a nozzle to an open space at~1 atm and re-enter to the vacuum through the ion sampling skimmer.…”
Section: Introductionmentioning
confidence: 99%
“…As a young graduate student, I was not aware of the pioneering experiments on atomic and molecular scattering conducted in Hamburg during the period 1926 to 1933 in Otto Stern's laboratory (6). But Kantrowitz's & Grey's 1951 paper (7), suggesting the use of nozzle beams, and the subsequent unsuccessful attempt by Kistiakowsky & Slichter (8) constructing a molecular-beam machine. As Greene later told me, they had already thought about doing something new in addition to shock waves (Greene) and studying transport processes (Ross).…”
Section: The Impact Of the Taylor And Datz Experiment: 1955mentioning
confidence: 99%
“…This section was headed by the French Alsatian Herman Hering, a man of great rigor who had survived a German concentration camp, and later by the excellent British chemist Jack Sutton. Since they had plenty of funding, I suggested that their new young scientist, Roger Campargue, should build a true molecular beam of the Kantrowitz & Grey type (93) and cross it with a controlled electron beam so as to do improved spectroscopic experiments, on cold supersonic molecular beams, with respect to my Orsay effusion devices. Campargue built the molecular beam but, to my increasing frustration, never did the crossed beam experiment.…”
Section: Back In France: Round About Benzene Benzyl and Some Molecumentioning
confidence: 99%